Supplementation of Olive Oil and Flaxseed Oil on Blood Pressure and Inflammation in Healthy and At-Risk Adults: A Systematic Literature Review and Meta-Analysis - McNabb, Tara B.; Young, Ian; Newman, Rachel G.; Skinner, Roy C.; Benedito, Vagner A.; Tou, Janet C. (Current Hypertension Reviews, 2024)
BackgroundAdding olive oil (OO) and flaxseed oil (FLO) to the diet has been reported to improve endothelial function and reduce inflammation. However, the efficacy of supplementing OO and FLO on blood pressure (BP) in normo-, pre-, and hypertensive stage 1 adults is uncertain.ObjectiveThis study aimed to systematically review the literature on OO and FLO supplementation on BP and select inflammatory markers in healthy adults and adults at risk of hypertension.MethodsFour databases, PubMed, CINHAL, Web of Science, and Medline (Ovid), were searched from inception until October 2023 for randomized control trials (RCTs) comparing OO and FLO supplementation in normotensive or adults at risk of hypertension. The outcomes included were systolic blood pressure (SBP) and/or diastolic blood pressure (DBP) and at least one inflammatory marker, C-reactive protein (CRP), interleukin6 (IL6), or tumor necrosis factor alpha (TNFα). The risk of bias was assessed using version 2 of the Cochrane risk of bias tool for RCTs, publication bias visualization was performed using funnel plots, and meta-analysis was completed to generate average estimates of effects in 2024.ResultsSeventeen RCTs, comprising 14 studies on OO and 3 on FLO, met the inclusion criteria. Meta-analysis using a random-effects model reported no significant effect on SBP n=17 mean difference (MD) -0.48; 95% CI: -1.76, 0.80; p=0.65, I2=0%) and DBP (n=16, MD -0.47; 95% CI: -1.33, 0.39; p=0.65, I2=0%) or inflammatory markers, CRP (n=8, MD 0.11; 95% CI: -1.18, 0.40; p=0.98, I2=0%), IL6 (n=3, MD -0.15; 95% CI: -0.57, 0.27; p=0.87, I2=0%), and TNFα (n=3, MD-0.08; 95% CI: -0.12, -0.03; p=0.98, I2=0%).ConclusionLonger-duration, higher-dose, and larger-scale RCTs are needed to better understand the efficacy of OO and FLO supplementation on BP. Further insight will better inform dietary supplement use for preventing hypertension.
Keywords: Olive oil